Rectal Radiation Dose and Clinical Outcomes in Prostate Cancer Patients Treated With Stereotactic Body Radiation Therapy With and Without Hydrogel - Kundu, Palak; Lin, Eric Y.; Yoon, Stephanie M.; Parikh, Neil R.; Ruan, Dan; Kishan, Amar U.; Lee, Alan; Steinberg, Michael L.; Chang, Albert J. (Frontiers in Oncology, 2022)
Background: Patients with prostate cancer treated with stereotactic body radiation therapy (SBRT) may experience gastrointestinal (GI) toxicity. The hydrogel may mitigate this toxicity by reducing the rectal radiation dose. The purpose of this study is to compare rectal radiation dose and GI toxicity in patients receiving prostate SBRT with and without hydrogel. Methods: Consecutive patients treated with SBRT between February 2017 and January 2020 with and without hydrogel were retrospectively identified. Baseline characteristics including prostate volume, rectal diameter, BMI, age, pre-treatment PSA, Gleason score, T-stage, and ADT usage were compared. Dosimetric outcomes (V40Gy, V36Gy, V32Gy, V38Gy, and V20Gy), rates of acute (≤90 days) and late (>90 days) GI toxicity, and PSA outcomes were evaluated for patients with and without hydrogel. Results: 92 patients were identified (51 hydrogel, 41 non-hydrogel). There were no significant differences in baseline characteristics. Rectal V38(cc) was significantly less in the hydrogel group (mean 0.44 cc vs mean 1.41 cc, p=0.0002), and the proportion of patients with V38(cc) < 2cc was greater in the hydrogel group (92% vs. 72%, p=0.01). Rectal dose was significantly lower for all institutional dose constraints in the hydrogel group (p<0.001). The hydrogel group experienced significantly less acute overall GI toxicity (16% hydrogel vs. 28% non- hydrogel, p=0.006), while the difference in late GI toxicity trended lower with hydrogel, but not statistically significant (4% hydrogel vs 10% non- hydrogel, p=0.219). At median follow-up of 14.8 months, there were no biochemical recurrences in either group. Conclusion: Hydrogel reduces rectal radiation dose in patients receiving prostate SBRT and is associated with a decreased rate of acute GI toxicity.